The Patterns of Early Childhood Media Consumption in the Digital Television Era - Suci Lukitowati; Widha Anistya Suwarso; Dea Varanida (Fakultas Dakwah UIN Saizu Purwokerto, 2022)
This study aims to analyze consumption patterns of children's programs on digital media in Indonesia. The research uses a qualitative approach with the uses and gratification theory as a theoretical framework—collecting research data through in-depth interviews with respondents. The research respondents were ten informants aged at least 21 years with children ranging in age from 2 to 6 years. The respondents were interviewed in-depth to get answers regarding the pattern of watching children's entertainment media shows in their respective homes. The study results reveal that parents choose television and YouTube as entertainment media for their early childhood. Parents give these two media because YouTube has three elements: interactivity, demassification, and asynchronous, while television is considered a counterbalance to smartphone addiction in children. The media consumption patterns of each family are remarkably diverse but have identical motives. The primary reason parents provide children's entertainment. Digital television has not been popular as an entertainment media option for early childhood.